The impact of nonprofit brand orientation on organisational performance - Napoli, Julie (Westburn Publishers Ltd, 2006)
Brands have become increasingly important to many nonprofit organisations. Consequently, brand orientation has emerged as an attractive business philosophy in this sector. In this study, the relationship between nonprofit brand orientation (NBO) and organisational performance is examined. Findings suggest that there is a positive association between the dimensions of NBO and nonprofit organisational performance. Further, successful nonprofit organisations tend to be more brand-oriented than their less successful counterparts. Limitations of the study are noted and suggestions for ongoing research offered.